Stability analysis of a fractional virotherapy model for cancer treatment - Tavoni, Robinson; Mancera, Paulo F.A. [UNESP]; Camargo, Rubens F. [UNESP] (Universidad Nacional de Colombia, 2021)
This paper presents a stability analysis of a differential equations model related to the cancer treatment with an oncolytic virus in its classical and fractional version via Caputo derivatives. Numerical simulations of three possible scenarios are presented and support the discussions on the advantages of using fractional modeling.